Penggunaan Media Pembelajaran Terhadap Keberhasilan Mapel PJOK pada Kelas IV SD Negeri 01 Banjarsari - Amat Muslim (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Physical education, sports and health (PJOK) subjects are very important subjects for students to learn, because with knowledge about health and sports practice students can fortify themselves, one of which is by increasing body resistance (immunity). Media has an important role in learning every lesson, including in the PJOK folder. The creativity of an educator is very important in the success of learning. Modification of media adapted to local wisdom will have a positive impact on student learning outcomes. The purpose of this article is to describe the importance of media on PJOK learning outcomes in schools. This writing was carried out by analyzing using the review method of references published online, related to learning media. Analysis of the positive impact on learning outcomes was also carried out. The results of the analysis show that research on the importance of learning media greatly influences the learning outcomes of PJOK. The development of PJOK media has been carried out extensively in various sports. The development of PJOK learning media is mostly done by utilizing interactive media in accordance with the development of information technology. The creativity of educators using the concept of local wisdom in modifying the media also greatly influences the learning outcomes of PJOK.